2015
DOI: 10.1097/pas.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

The High-grade (WHO G3) Pancreatic Neuroendocrine Tumor Category Is Morphologically and Biologically Heterogenous and Includes Both Well Differentiated and Poorly Differentiated Neoplasms

Abstract: Background The 2010 WHO classification recommends that pancreatic neuroendocrine tumors should be graded based on mitotic rate and Ki67 index, with grade 2 (G2) pancreatic neuroendocrine tumor (PanNET) defined as having a mitotic rate of 2–20 mitotic figures/10 high power fields (HPF) or a Ki67 index of 3–20%. Grade 3 (G3) pancreatic neuroendocrine carcinoma (NEC) is defined as having >20 mitotic figures/10 HPF or a Ki67 index of >20%. However, some PanNETs show discordance between the mitotic rate and Ki67 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
334
4
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(358 citation statements)
references
References 7 publications
15
334
4
5
Order By: Relevance
“…Prints were coded and randomly used for manual counting of Ki67 LI. Counting was performed by manual marking of tumoral cells with and without Ki67 expression with color pens [21,38]. Of note, this approach is a reference technique of Ki67 LI assessment in pancreatic NEN [21].…”
Section: Ki67 LI Scoringmentioning
confidence: 99%
“…Prints were coded and randomly used for manual counting of Ki67 LI. Counting was performed by manual marking of tumoral cells with and without Ki67 expression with color pens [21,38]. Of note, this approach is a reference technique of Ki67 LI assessment in pancreatic NEN [21].…”
Section: Ki67 LI Scoringmentioning
confidence: 99%
“…Recent studies have shown a significantly longer survival for these patients in comparison with patients with true poorly differentiated NEC, although their clinical outcome is slightly worse than those with grade 2 NET. 210,211 These data thus suggest that grade 3 neuroendocrine neoplasms are heterogeneous. Tumors with well-differentiated morphology but with grade 3 Ki-67 proliferation index should be separated from true poorly differentiated NECs, and they may be more appropriately designated as ''well-differentiated NET with an elevated proliferation rate.''…”
Section: Grading Neuroendocrine Neoplasms By Ki-67mentioning
confidence: 85%
“…Tumors with well-differentiated morphology but with grade 3 Ki-67 proliferation index should be separated from true poorly differentiated NECs, and they may be more appropriately designated as ''well-differentiated NET with an elevated proliferation rate.'' 210 Nevertheless, Ki-67 proliferation index has important therapeutic and prognostic implications. Data from a study on a large number of patients with GI NEC (grade 3) have shown less responsiveness to platinumbased chemotherapy but longer survival in patients with Ki-67 index less than 55%.…”
Section: Grading Neuroendocrine Neoplasms By Ki-67mentioning
confidence: 99%
“…Although the most recent WHO classification implied that all G3 neuroendocrine neoplasms are poorly differentiated neuroendocrine carcinomas, emerging data indicate instead that some G3 cases remain well differentiated [11]. These cases (G3 well-differentiated GEP-NETs) generally have histologic features in common with other well-differentiated NETs, and in most cases, only the Ki67 index-not the mitotic rate-falls in the G3 range.…”
mentioning
confidence: 99%